Hazel Bell, and seven unidentified women pose in front of a Y.W.C.A. sign. - Unknown:::Creator::::::::::::
Photograph shows eight women posing for a picture in front of a sign posted on a building. Seven women make up the first row, and there is one person in the second row. There is also a man with his back to the camera walking past the group. The readable portion of the sign says Y.W.C.A. Hazel Bell is one of the women in the photograph.